Evaluation of surgical risk and prognosis between thyroid nodules of size <1 and ≥1 cm - Ma, Jia-Min (Gland Surg, 2019)
BACKGROUND: The objective of this study was to evaluate the surgical risk and prognosis between thyroid nodules of size <1 and ≥1 cm and to explore whether it is reasonable generally to ignore the diagnosis and treatment of thyroid nodules and thyroid carcinoma <1 cm in wide areas of China. METHODS: A retrospective observational study included all first-time thyroid surgery patients between January 2005 and December 2016 of the First Affiliated Hospital of Harbin Medical University. All patients were divided into two groups (group A: <1 cm, group B: ≥1 cm) according to the maximum diameter of the nodules and demographics, surgery procedure, pathology, postoperative complications, morbidity, and mortality were analyzed. RESULTS: A total of 6,317 patients were reviewed and 3,424 (54.20%) of them were malignant; 2,128 patients in group A and 4,189 in group B. Patients in group A had better pathological diagnosis, inferior extent of lymph node metastasis, less surgical complexity, fewer postoperative complications, and longer disease-free survival (DFS). CONCLUSIONS: Thyroid operations were safer and involved fewer postoperative complications when thyroid nodules were <1 cm and patients who were diagnosed with malignant thyroid disease had superior prognoses. Underdeveloped regions of China should diagnose and treat thyroid nodules <1 cm early.